ANALISISIS PERMASALAHAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SD NEGERI PURWOSARI - Adnyana, Made Sudimerta; Kertayasa, I Ketut; Sudarsana, Wayan (JATMIKA : Journal Education and Learning of Elementary School, 2025)
This study aims to analyze and identify teacher problems, strengths and weaknesses, teacher understanding and readiness in implementing the independent curriculum at Purwosari State Elementary School. The method used in this study is a descriptive qualitative method. the problems experienced include: lack of understanding of the implementation of the Independent Curriculum, problems in implementing P5, lack of teacher ability in using technology, lack of supporting infrastructure in learning and filling out report cards which are quite complicated. In its implementation, the Independent Curriculum has advantages such as the existence of PMM, the existence of P5 learning, teachers and students are given freedom in the teaching and learning process. While the disadvantages of the independent curriculum include: a lot of administration, lack of references, and more time consuming. Regarding understanding and readiness, teachers have sufficient understanding of the concept of the Independent Curriculum but are lacking in its implementation and for teacher readiness it shows that teachers are not fully ready to implement the Independent Curriculum.